Features of Company Management in the Field of E-Commerce - T. I. Marchenko; A. O. Ryahovskij (Управленческие науки)
The relevance of the research topic is due to the increasing spread of e-commerce. For the effective development of a company in this area, a strategy with certain features is necessary, and the purpose of the study is to determine the author’s concept of its development. The article reflects the most important stages of this process, defines the main competencies of developers. When forming the strategy, the following aspects were taken into account: a short period of time allowed for making managerial decisions; the need for highly qualified personnel developing a strategy, carrying out promotion and contacting the consumer, as well as the fact that innovations, the search for free markets serve as a source of development for e-commerce companies, which corresponds to the strategy of the “blue ocean”. The study was carried out using methods such as analysis and synthesis, induction and deduction, a systematic approach the authors analyzed an array of scientific publications on the topic under study. The results of the work are of practical value for specialists involved in strategic planning in the field of e-commerce, as well as for the researchers and students interested in the issues discussed in the article.